Analysis Numerical Literacy Ability in Middle School Students in Material Set - Ulfa Luthfiani; Sehatta Saragih; Elfis Suanto; Maimunah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study identified the numeracy literacy skills of Almuttaqin MTS students in a rigid material. A hallmark of numeracy literacy is the capacity to apply numbers and related symbols to operations on algebraic forms, analyze data, and understand analysis findings to predict and make judgments. Tests and interviews were used to collect data, which were then analyzed through data reduction, presentation, and conclusion. Based on the findings, the numeracy literacy skills of MTS Almuttaqin students, one student (4%) is included in the excellent group for numeracy literacy, nine students (34%) are included in the excellent category, 15 students (50%) are included in the good category, and five students (11)% is included in the less category. Students with high numeracy literacy (ST) can use various numbers and symbols to solve problems, analyze information to make predictions, evaluate the findings of their analysis, and make decisions when handling the challenges of the given material. Using various numbers and symbols to solve problems and analyze information is the only marker that satisfies students with moderate numeracy literacy (SD). They have not yet reached the stage where they can make the best choices regarding their assigned content. Students with limited numeracy literacy (SR) only write numbers and are identified when completing assignments. As a result, SD and SR have not fully learned numeracy skills. The indications that were not fulfilled were caused by mistakes made by students, including not carefully recording known and asked data, choosing an inappropriate problem-solving approach, and not understanding ideas well enough to answer questions problem.